Dampak Lingkungan Kerja dan Etos Kerja Terhadap Kinerja Pegawai - Dolonseda, Herman Philips; Watung, Sjeddie R (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2020)
This study aims to determine the effect of work environment and work ethic on employee performance in the Regional Education and Culture Office of Sangihe Islands Regency. This study used a survey research method, where the research instrument was a tested questionnaire and met the validity and reliability test requirements. Data were analyzed using multiple regression analysis. The population in this study were all employees at the Education and Culture Office of the Sangihe Islands Regency totaling 70 people, while the number of samples was 60 people. The results show that there is an influence of the work environment on the performance of employees at the Regional Education and Culture Office of the Sangihe Islands Regency, there is an influence of work ethic on the performance of employees at the Regional Education and Culture Office of the Sangihe Islands Regency, and there is a joint influence on the work environment and work ethic on the performance of employees at the Regional Education and Culture Office of Sangihe Islands Regency.